Study of population structure of Ferula foetida(Bunge) Regel in the conditions of Mangystau region - Sagyndykova, M.S.; Imanbayeva, A.A.; Ishmuratova, M.Yu. (Fundamental and Experimental Biology, 2019)
Results of a research of a condition of populations of Ferula foetida (Apiaceae family) in the territory of Mangystau region are given in the article. The composition, structure of populations, polymorphism, and condition of growth and peculiarities of the natural populations of Ferula foetidais studied. The general projective covering in community was from 35 to 80 %. Occurrence of samples of Ferula foetida was 0.1–0.8 pieces/sq.m. In natural populations all age states (from 1 year old to 7 years old individuals) are revealed; in a generative phase 5-6-7 years old individuals are noted. On the various populations 15–55 % of plants are observed in blossoming phase, other plants were in a phase of the radical leaf bascket. The ratio of the main age groups of plants on each described population is defined, the phytocenotic structure and some morphological indicators of elevated bodies is conducted. The received results of phytocenotic descriptions testify to a possibility of practical using of natural population of Ferula foetida.